Role of dental sleep medicine in management of patients with obstructive sleep apnea disorders using a team approach. (17th November 2018) - Nakai, Takayuki; Matsuo, Akira; Takata, Yoshifumi; Usui, Yasuhiro; Kitamura, Koichi; Chikazu, Daichi
Abstract: Objective: Obstructive sleep apnea (OSA) is a significant social and health issue. An integrated multidisciplinary approach to OSA management may be the most effective owing to its multifactorial etiology. In this study, we evaluated the frequency and efficacy of various treatment modalities for OSA administered via an integrated care delivery model, and assessed the role of dental sleep medicine as part of a multidisciplinary team. Materials and Methods: We retrospectively evaluated 1115 patients with OSA treated at the Tokyo Medical University Hospital's Outpatient Clinic for OSA by a multidisciplinary team under one roof. The various treatment methods included the following: continuous positive airway pressure (CPAP), oral appliance (OA), surgery, and behavioral treatment. Results: The patient number of study group was as follows: 771 (69.1%) CPAP; 240 (21.5%) OA; 76 (6.8%) behavioral treatment and 28 (3%) surgery. Because significantly fewer patients underwent surgery, there was a discrepancy between the recommended first-choice treatment and the actual treatment. A statistically significant number of younger patients in each treatment group underwent surgery. Success rate of OA and MMA were 74.4 and 80%, respectively. Conclusions: Proper selection of primary treatment to manage patients with OSA was possible under one-roof system that included dental sleep medicine.